REM Sleep Fragmentation in Patients With Short-Term Insomnia Is Associated With Higher BDI Scores - Wu, Danjuan; Tong, Maoqing; Ji, Yunxin; Ruan, Liemin; Lou, Zhongze; Gao, He; Yang, Qing (Frontiers in Psychiatry, 2021)
Objective: To observe the changes in sleep characteristics and BDI scores in patients with short-term insomnia disorder using a longitudinal observational study. Methods: Fifty-four patients who met the criteria for short-term insomnia disorder (SID) of the International Classification of Sleep Disorders, Third Edition (ICSD-3) were recruited. Depression levels were assessed using the Beck Depression Inventory (BDI) at enrollment and after 3 months of follow-up respectively. Sleep characteristics were assessed by polysomnography. Results: After 3 months of follow-up, the group was divided into a SID with increased BDI score (BDI > 15) and a SID with normal BDI score (BDI ≤ 15) according to the total BDI score of the second assessment. The differences in REM sleep latency, REM sleep arousal index and NREM sleep arousal index between the two groups were statistically significant. The total BDI score was positively correlated with REM sleep arousal index and NREM sleep arousal index, and negatively correlated with REM sleep latency, which were analyzed by Pearson Correlation Coefficient. Multiple linear regression was used to construct a regression model to predict the risk of depression, in which the prediction accuracy reached 83.7%. Conclusion: REM sleep fragmentation is closely associated with future depressive status in patients with short-term insomnia disorder and is expected to become an index of estimating depression risk.